2017
DOI: 10.1016/j.ebiom.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Subtherapeutic Antibiotics Aggravates Ischemic Stroke Outcome in Mice

Abstract: Subtherapeutic antibiotics have been widely used in agriculture since the 1950s, which can be accumulated in human body through various approaches and may have long-term consequences. However, there is limited information about the link between chronic subtherapeutic antibiotic exposure and the outcome of ischemic brain injury. Here we showed that long-term treatment with subtherapeutic chlortetracycline, penicillin or vancomycin, which were widely used in agriculture approved by US Food and Drug Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…We also find that carbon metabolism, with 15 enriched proteins, is the main metabolic pathway. It contributes to complex biological processes that suppress neuroinflammation, induction of hypoxia, and apoptosis, which is consistent with previous studies (Dong et al, 2017;Fedorovich et al, 2017;Correa-Costa et al, 2018). Our analysis reveals that most of the proteins were downregulated in these pathways, implying their important role in binding, metabolism and brain development, response to drug, and the immune system.…”
Section: Discussionsupporting
confidence: 91%
“…We also find that carbon metabolism, with 15 enriched proteins, is the main metabolic pathway. It contributes to complex biological processes that suppress neuroinflammation, induction of hypoxia, and apoptosis, which is consistent with previous studies (Dong et al, 2017;Fedorovich et al, 2017;Correa-Costa et al, 2018). Our analysis reveals that most of the proteins were downregulated in these pathways, implying their important role in binding, metabolism and brain development, response to drug, and the immune system.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, long‐term administration of vancomycin actually impairs endothelial cell function in mice (Dong et al . ). Thus, if anything, it is possible that the antibiotic cocktail used may have exerted adverse direct effects on arterial function that countered the beneficial effects of gut microbiome suppression.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, several studies examined the impact of antibiotic treatment on the outcomes in hosts with ischemic brain injury. For example, Benakis et al (2016) reported that orally administered amoxicillin/clavulanic acid reduces ischemic brain injury in mice by regulating gut microbiota composition, while Dong et al (2017) reported that orally prophylactic treatment with an antibiotic cocktail consisting of chlortetracycline, penicillin VK, and vancomycin could not reduce microbial infection, and Winek et al (2016) reported that the depletion of gut microbiota by oral prophylactic treatment with an antibiotic cocktail consisting of ampicillin, vancomycin, ciprofloxacin, imipenem, and metronidazole deteriorates the outcome after murine stroke. Singh et al (2016) reported that fecal microbiota transplantation of healthy mice into middle cerebral artery (MCA) occlusion-operated mice alleviated the stroke outcome.…”
Section: Introductionmentioning
confidence: 99%